Establish and Implement PAM and PRM ISO 20000-1:2011 - Najoan, Harvard K.; Mawuntu, Denny J. (Brilliance: Research of Artificial Intelligence, 2023)
Most enterprises are now using information technology services as their assets to support business objectives. These kind of services are provided by internal service provider (inside enterprise) or external service provider (outside enterprise). To deliver quality information technology services, service provider (which from now on will be called “organization”) either internal or external, must have standard for service management system. At present, the standard that is recognized as best practice for service management system for organization is international standard ISO/IEC 20000:2011. The most important part of this international standard is the first part or ISO/IEC 20000-1:2011-Service Management System Requirement, because it contains 22 for organization processes as requirement to be implemented in organizational environment in order to build, manage and deliver quality service to customer. Assessing organization management processes is the first step to implement ISO/IEC 20000:2011 into the organization management processes. This assessment needs Process Assessment Model (PAM) as assessment instrument. PAM comprises two parts: Process Reference Model (PRM) and Measurement Framework (MF). PRM is built by transforming the 22 process of ISO/IEC 20000-1:2011 and MF is based on ISO/IEC 33020. This assessment instrument was designed to assess the capability of service management process in Divisi Teknologi dan Sistem Informasi (Information Systems and Technology Division) as an internal organization of PT Pos Indonesia. The result of this assessment model can be proposed to improve the capability of service management system.